The Impact of Parenting on Children's Problematic Behavior: A Behavioristic Analysis of The Character Zain Al-Rafeea in The Film Capernaum - Sari, Eky Adelia; Muthohar, Sofa (Bulletin of Counseling and Psychotherapy, 2024)
This study will examine the problematic behaviors exhibited by the character Zain Al-Rafeea in the film Capernaum, analyzing these behaviors as a consequence of the parenting patterns employed by his parents. The method used in analyzing problematic characters and behavior is by using the behavioristic analysis method, which examines the relationship between stimuli and responses to understand how parenting influence shapes behavior. The approach used in this study is qualitative using library research with data collection techniques through observation and documentation in the Capernaum film which will be presented in descriptive form. The results of this research show that the problematic behavior shown by Zain Al-Rafeea, such as stealing, speaking harshly, running away from home, and getting involved in physical conflict with adults, is a conditioned response that is attached and connected to the stimulus resulting from his parents' parenting style. The results of this study are expected to contribute to the fields of education, psychology, and child welfare by identifying risk factors that contribute to the emergence of problematic behavior in children. This study is also expected to increase public awareness of the importance of positive parenting patterns in shaping healthy child development.